2017
DOI: 10.1155/2017/7916348
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Growth Retardation in Children Suffering from Sickle Cell Anemia: First Report from Central Africa

Abstract: Background. The aim of this study was to investigate and determine the risk factors associated with poor growth among SCA children. Methods. A cross-sectional study was conducted in Kinshasa, the capital's country. The nutritional status was assessed using the Z scores of the anthropometric indices. Results. We gathered data on the 256 patients, 138 females (53.9%), who entered the study. The mean age at presentation was 8.4 ± 4.9 years of age. Underweight, stunting, and wasting were found, respectively, in 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
3
20
2
Order By: Relevance
“…In the studied population, living in West and Central Africa, more than half of patients with SS or Sb 0 phenotypes and more than one third of patients with SC or Sb + phenotypes suffered from growth failure. Growth failure was significantly more frequent in SS and Sb 0 phenotypes, whereas it was similar in SC, Sb + phenotypes and healthy subjects, as previously described in different countries (Platt et al, 1984;Stevens et al, 1986;Singhal et al, 1994;Chawla et al, 2013;Lukusa Kazadi et al, 2017). The greatest difference in growth failure frequency compared to non-SCD controls was observed during adolescence, between 12 and 18 years of age.…”
Section: Discussionsupporting
confidence: 84%
“…In the studied population, living in West and Central Africa, more than half of patients with SS or Sb 0 phenotypes and more than one third of patients with SC or Sb + phenotypes suffered from growth failure. Growth failure was significantly more frequent in SS and Sb 0 phenotypes, whereas it was similar in SC, Sb + phenotypes and healthy subjects, as previously described in different countries (Platt et al, 1984;Stevens et al, 1986;Singhal et al, 1994;Chawla et al, 2013;Lukusa Kazadi et al, 2017). The greatest difference in growth failure frequency compared to non-SCD controls was observed during adolescence, between 12 and 18 years of age.…”
Section: Discussionsupporting
confidence: 84%
“…In the absence of normative size data for age (Kazadi et al, 2017) in our population, we could not verify the assertion regarding the significant relationships observed between BMD and low height for age, weight for age and BMI for age reported in several SCA studies (Henderson et al, 1994;Luban et al, 1982;Barden et al, 2000;Meeuwes et al, 2013;Bullamore et al, 1970;Lal et al, 2006;Miller et al, 2006;Baldanzi et al, 2011) but also between BMI and BMD in the general population (Kabeya et al, 2017).…”
Section: Discussioncontrasting
confidence: 56%
“…Other studies have found no relationship between height or BMI and BMD (Chapelon et al, 2009;Lal A et al, 2006;Sarrai et al, 2006). The present study did not seek to evaluate the quantity and the quality of the food intake of our subjects who are considered weak (Kazadi et al, 2017), Therefore, we can not determine the contributions of calories, calcium, microelements or vitamin D in the disclose of low BMD.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations